AL-TARAKIIB AL-‘ARABIYYAH AL-MUSTA’MALAH FII AL-LUGHAH AL-INDUUNISIYYAH: ‘ADDADUHA WA ANWAA’UHA WA KHASHAAISHUHAA - Lubis, Torkis (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
This article describes Arabic phrase and sentence adopted from Bahasa Indonesia to answer three main questions on language absorption, mainly:Â  how many Arabic phrase and sentences adopted in Bahasa Indonesia? What kind of Arabic phrases and sentences adopted inÂ  Bahasa Indonesia? What are the changes in the Arabic phrases and sentences adopted in Bahasa Indonesia? This is a library research by collecting all the Arabic phrases and sentencesÂ  found in Bahasa Indonesia compiled in the main resources, â€œKamus Bahasa Indonesia Kontemporerâ€ by Drs. Peter Salim and Yenny Salim, books on religion, literature, magazine, newspaper, speech in Bahasa Indonesia and conversation among speaker ofÂ  Bahasa Indonesia as the secondary resource. The finding of research says that the number of Arabic phrase and sentences adopted in Bahasa Indonesia is 505 phrases or idiomatic sentences.Â  The phrases and sentences have been adjusted in three aspects, mainly: phonetic, syntacticalÂ  and semantic.Keywords: Tarakiib, Taâ€™tsiir, Al-Lughah Al-Indunisiyyah